2011
DOI: 10.3747/co.v18i3.755
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Recommendations for the Treatment of Recurrent or Progressive Glioblastoma Multiforme

Abstract: Recommendation 1: Multidisciplinary Approach: To optimize treatment outcomes, the management of patients with recurrent glioblastoma should be individualized and should involve a multidisciplinary team approach, including neurosurgery, neuropathology, radiation oncology, neuro-oncology, and allied health professions. Recommendation 2: Imaging: The standard imaging modality for assessment of recurrent glioblastoma is Gd-enhanced magnetic resonance imaging (MRI). Tumour recurrence should be assessed according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 121 publications
(106 reference statements)
0
75
0
1
Order By: Relevance
“…The clonogenic assay is a central test that shows the long-term survival and self-renewal of individual cells after treatment. 36 When comparing the results of proliferation with clonogenic capacity, differences can be seen; however, this could be explained by the different methodologies. Once proliferation with XTT is measured, the metabolism of cells and clonogenic capacity only measure the number of colonies with more than 50 cells, reflecting the cell renewal of cells.…”
Section: Polo-like Kinase and Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The clonogenic assay is a central test that shows the long-term survival and self-renewal of individual cells after treatment. 36 When comparing the results of proliferation with clonogenic capacity, differences can be seen; however, this could be explained by the different methodologies. Once proliferation with XTT is measured, the metabolism of cells and clonogenic capacity only measure the number of colonies with more than 50 cells, reflecting the cell renewal of cells.…”
Section: Polo-like Kinase and Radiationmentioning
confidence: 99%
“…In view of this, multimodality therapy for GBM has previously been demonstrated to improve a patient's survival, as has already been proposed by several authors and including the Canadian committee. 36,38 Several phase II trials have shown synergistic or additive effects of many drugs with different mechanisms of action when combined with radiation and Temozolomide in GBM [39][40][41] though, in practice, some of these tests have not been promising. Currently, new kinase inhibitors are being tested in combination with Temozolomide and radiation for cancer treatment; among them, it has been reported that Aurora kinase inhibitors could be suitable for use as chemoadjuvant treatment in GBM.…”
Section: Pezuk Et Almentioning
confidence: 99%
“…According to those guidelines, true disease progression within 12 weeks of chemoradiotherapy completion (when pseudoprogression is most prevalent) can be diagnosed only if the lesions are outside the radiation field (beyond the high-dose region or the 80% isodose line) or if unequivocal evidence of viable tumour is found on histopathology. Current Canadian treatment guidelines also advocate waiting for 3 cycles of adjuvant therapy after chemoradiotherapy to determine if gbm is truly progressing 9,10 . However, the time interval (about 2 months) required to differentiate pseudoprogression from true progression is often distressing for both the patient and the oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…By Stupp and coworkers, it was shown in a randomized study that treatment with oral Temozolomide, a cytostatic drug, acting as an alkylating agent, leads to a limited, yet significant prolongation of survival with acceptable toxicity. Previously, for example a large clinical study examining combined Procarbacin, CCNU (Lomustin) and Vincristin (PCV), had reported a very modest gain of survival with radiotherapy plus PCV versus 13 months with radiotherapy alone; however, the toxicity connected with such a therapy approach led to a significant debate regarding the actual benefit for the patient [1,3,7,8]. In children, systemic approaches have already been standard in therapy back from the nineties, however, here, the cure rate was also dismal -although in general, it is slightly better than in adults [9].…”
Section: Glioblastoma: a Scourge To Mankindmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) accounts for up to 60% of all malignant primary brain tumours in adults [1,2,3] with 2-3 cases per 100,000 inhabitants per year in Europe or North America, while in children it accounts for only about 5 % of the brain tumors, with an incidence even below 0.1 per 100,000 inhabitants [4,5].…”
Section: Glioblastoma: a Scourge To Mankindmentioning
confidence: 99%